Envelhecimento: considerações a partir do conhecimento entre estudantes de graduação e fonoaudiólogos - Garcia, Ana Carla Oliveira (2021)
Literature suggests that negative attitudes toward the elderly may have adverse effects, especially in health care settings and in rehabilitation. Little is known about the knowledge of speech therapists about the aging process. Objective: The purpose of this investigation was to examine the knowledge about aging in professionals and a group of undergraduate students enrolled in an accredited speech-language pathology program to determine if the degree of ageism differed based on gender, age or previous experience working with older adults. Method: This is a descriptive crosssectional study with 102 students and 120 speech therapy professionals. Data were collected through a sociodemographic questionnaire and a questionnaire to assess gerontological knowledge (adapted by KOSCH et al 2007 from the "Palmore Aging Quiz"). Results: The data was analyzed using descriptive statistics and analysis odds ratio calculated for effect size between groups. The age of speech language pathology students and the average years of education is lower than of speech therapists. A higher prevalence of students who do not have knowledge about aging process is observed. Regarding questions Q7 and Q14, participants who lack knowledge about the aging process is higher among speech therapists. For questions Q12, Q15, Q16, Q17, Q18, Q20 e Q23 there were no difference among speech therapists and undergraduate students. Regarding other questions, a higher prevalence of students who do not have knowledge about the aging process is observed. There was no significant effect for the descriptive variables such as living with the elderly, work or academic experience about not having knowledge about aging, for each of the 23 questions among students and speech therapists. Conclusion: When compared with the group of speech therapists, it’s observed that more undergraduate students don’t have knowledge about the aging process